Revitalisasi Perpustakaan Sekolah Untuk Meningkatkan Minat Literasi Siswa di Sekolah Dasar - Fasica, Nani Farah; Puspitanigtyas, Amalia Risqi; Jannah, Fitriatul; Holila, Nur (Universitas Negeri Makassar, 2024)
This research examines the revitalization of school libraries to increase students' interest in literacy at SDN 4 Dawuhan, Situbondo Regency. The library is a place to find important information that students need in learning activities. Based on the results of observations obtained at SDN 4 Dawuhan, the libraries in schools require revitalization or library renewal activities. Revitalization activities that must be carried out at the SDN 4 Dawu-han library are updating facilities and infrastructure, classifying book collections according to their type based on DDC (Dewey Decimal Classification), numbering master books, arranging collection books on bookshelves according to their type, and making special visit schedules for students in each class, library visit scheduling activities are carried out so that students can evenly make library visits , with this it is hoped that it can increase students' interest in literacy at SDN 4 Dawuhan, Situbondo Regency.